Prognostic Utility of Oculomotor Assessments in Determining Return-to-Learn Time in Acutely Concussed College Student-Athletes: A Pilot Study - Maya Vanderhorst; Alex Rawlings; Megan Germansky; Ayana Chodak; Amanda Krohn; Melissa Wilson; Robert Bauman; Benjamin Emke; Robert Parody; Zachary W. Bevilacqua (Neurotrauma Reports, 2023)
We sought to discover which oculomotor test (King-Devick [KD], near point of convergence [NPC], and accommodative facility [AF]) would best produce a prognostic model for an RTL time frame. An observational cohort design was used to longitudinally track division I and III student-athletes with concussion at a private university in New York State. Measurements included pre-RTL oculomotor testing (NPC, KD, and AF), along with daily text messages and phone calls. Participants were considered returned-to-learn once they had returned to baseline symptoms and had attended 2 days of classes. Our data promote KD score and class attendance as the best-fit prognostic model, with every second accrued on the KD test equating to 5.29?h of RTL time. Further, attending class throughout recovery, versus not, shortened RTL time by a mean 170.50?h, or 7.1 days. Five variables produced a significant attenuating association with concussion symptoms: time post-injury (p?=?0.01); caffeine (p?=?0.05); alcohol (p?=?0.01); music (p?=?0.01); and physical activity (p?=?0.01). Three variables produced a significant worsening association with concussion symptoms: screen time (p?=?0.05); music (p?=?0.01); and class attendance (p?=?0.01). The findings present a preliminary evidence-based model to prognosticate RTL time. To our knowledge, this is the second longitudinal study, and the first overall, to present objective data for guiding and prognosticating RTL, respectively. Correspondingly, these data should assist clinicians with objectively steering RTL in-clinic.